OVERVIEW ABOUT POSSIBILITIES AND AESTHETIC REHABILITATION LIMITATIONS IN SOME DENTAL DISORDERS - Irina Gradinaru; Alice Arina Ciocan Pendefunda; Hurjui Loredana Liliana; Adina Oana Armencia; Antohe Magda Ecaterina (Romanian Dental Association for Education, 2020)
The stomatognathic system comprises a wide variety of tissues and organs with different functions, but which contribute to the achievement of system-specific functions. Relationships are established between the various elements of the stomatognathic system and mechanisms for maintaining an intrasystemic balance are established biologically and mechanically. Affecting but one of the system component means, sooner or later, the imbalance of the whole system, simulating, meanwhile, the rebalancing systems. The absence of teeth on the ark gives edentulousness which, both untreated and treated incorrectly and incompletely, causes complications, sometimes difficult to neutralize: local (abrasion of remaining teeth, odonto-periodontal overload, changes in the morphology of the dental arch through migration, extrusions); loco-regional (mandibular-cranial malrelations); general (psychic, digestive). As long as the masticatory forces act with physiological intensity, intermittently and in the normal direction, a balance is maintained, the tooth not undergoing any change, the processes of apposition and resorption interacting favorably with each other.